RESEARCH POLYMER COATINGS. MATERIAL PROPERTIES AND APPLICATION FEATURES - Makhammadjanov Khusanboy Alisher o‘g‘li; Mamatalieva Zulfiyakhon Khusanovna; Kamolov Khojikamol Adhamjon o‘g‘li (International Journal of Innovations in Engineering Research and Technology, 2021)
This article describes the coating processes on the working surfaces of many parts from different polymeric materials. Obtaining coatings from polymers is superior to other coatings in terms of quality, efficiency and low cost. coatings made of polymer composite materials in order to protect working surfaces from corrosion and increase the durability of service parts made of metals.